Study Of Column Evaluation Of Capacity On Earthquake Load In Level Building - Yoab Orlando Iek; Koespiadi Koespiadi (Journal of World Conference (JWC), 2020)
Column play an important role in bulding structure,remembering column failures wil improve the overall structure.other structure,column structural element that are vulnerable to completion failure recive earthquake loads.The structure of this bulding is located in jayapura,including in KDS D with a value of = 0,9 and =0.96 .From the result of structural analysis to the column evaluated,then the dimension of K1 100/100 (28D36,D25-100 mm , D25-150 mm and 8 D25-100 mm) K2 120/120 (28D32, D25-100 mm,D25-150 mm and 8 D25-100 mm) ,K3 130/130 (28 D 32,D25-130 mm, D25-150 and 8D25-130 mm),K4 140/140( 28 D32,D25-130 mm,D25-150 mm and 8D25-130 mm), column WF792x400x30x40, WF 800x400x30x40, WF 808x400x30x40, WF 900x400x30x40 with efficient columns such as column K1 100/100 with low prices Rp Rp.23,065,074,774.000.After analyzing the structure of a tiered bulding using the SRPMK method,it is expected to remain earthquake resisitant and have economic efficiency values